1994
DOI: 10.1111/j.1559-1816.1994.tb01552.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Physical Attractiveness, Race, Socioeconomic Status, and Gender of Defendants and Victims on Judgments of Mock Jurors: A Meta‐Analysis1

Abstract: A meta‐analysis of experimental research on mock juror judgments was conducted to assess the effects of physical attractiveness, race, socioeconomic status (SES), and gender of both defendants and victims to test the theory that jurors use characteristics that are correlated with criminal behavior as cues to infer guilt and to recommend punishment. In general, it was advantageous for defendants to be physically attractive, female, and of high SES, although these advantages were nil for some crimes. There were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
269
9
7

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(303 citation statements)
references
References 29 publications
18
269
9
7
Order By: Relevance
“…Further, these effects have not only been found to operate within jurors but also within judges (Downs & Lyons 1991;Zebrowistz & McDonald, 1991). Mazzella and Feingold's (1994) meta-analysis concluded that, on average, it is advantageous for defendants to be physically attractive.…”
Section: The Attraction Leniency Biasmentioning
confidence: 99%
“…Further, these effects have not only been found to operate within jurors but also within judges (Downs & Lyons 1991;Zebrowistz & McDonald, 1991). Mazzella and Feingold's (1994) meta-analysis concluded that, on average, it is advantageous for defendants to be physically attractive.…”
Section: The Attraction Leniency Biasmentioning
confidence: 99%
“…Extant research has established that jurors are often influenced by not only the facts in a case, but extralegal factors (e.g., attractiveness, gender) that have no bearing on the case itself (e.g., Mazzella & Feingold, 1994;Peace & Forrester, 2012). One such factor under investigation in the present study is the emotionality of a claim and whether this influences witness credibility.…”
Section: Introductionmentioning
confidence: 98%
“…Some researchers have concluded that racial effects can be erased by judicial instruction (Pfeifer & Ogloff, 1991), by deliberation (Bernard, 1979), or by the absence of inadmissible evidence (Johnson, Whitestone, Jackson, & Gatto, 1995). Still other studies and meta-analyses find no evidence of racial bias (Mazzella & Feingold, 1994;McGuire & Bermant, 1977).…”
Section: Jurydecisionmakingisacomplexsetofpsychologicalmentioning
confidence: 99%